Distinct Patterns of Rhizosphere Microbiota Associated With Rice Genotypes Differing in Aluminum Tolerance in an Acid Sulfate Soil - Xiao, Xun; Wang, Jia Lin; Li, Jiao Jiao; Li, Xiao Li; Dai, Xin Jun; Shen, Ren Fang; Zhao, Xue Qiang (Frontiers in microbiology, 2022)
Rhizosphere microbes are important for plant tolerance to various soil stresses. Rice is the most aluminum (Al)-tolerant small grain cereal crop species, but the link between rice Al tolerance and rhizosphere microbiota remains unclear. This study aimed to investigate the microbial community structure of aluminum-sensitive and Al-tolerant rice varieties in acid sulfate soil under liming and non-liming conditions. We analyzed the rice biomass and mineral element contents of rice plants as well as the chemical properties and microbial (archaea, bacteria, and fungi) communities of rhizosphere and bulk soil samples. The results showed that the Al-tolerant rice genotype grew better and was able to take up more phosphorus from the acid sulfate soil than the Al-sensitive genotype. Liming was the main factor altering the microbial diversity and community structure, followed by rhizosphere effects. In the absence of liming effects, the rice genotypes shifted the community structure of bacteria and fungi, which accounted for the observed variation in the rice biomass. The Al-tolerant rice genotype recruited specific bacterial and fungal taxa ( Bacillus , Pseudomonas , Aspergillus , and Rhizopus ) associated with phosphorus solubilization and plant growth promotion. The soil microbial co-occurrence network of the Al-tolerant rice genotype was more complex than that of the Al-sensitive rice genotype. In conclusion, the bacterial and fungal community in the rhizosphere has genotype-dependent effects on rice Al tolerance. Aluminum-tolerant rice genotypes recruit specific microbial taxa, especially phosphorus-solubilizing microorganisms, and are associated with complex microbial co-occurrence networks, which may enhance rice growth in acid sulfate soil.